2003
DOI: 10.1248/cpb.51.1417
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Constituents of Gardenia Species. III. New Iridoid Glycosides from the Leaves of Gardenia jasminoides cv. fortuneana HARA

Abstract: We have reported the isolation of 13 new terpenoids from Gardeniae Fructus [the fruit of Gardenia jasminoides ELLIS (Rubiaceae)], known as the Shan-zhi-zi (in Chinese) herbal drug, and it has been used for its antiphlogistic, diuretic, and cholagogue effects. 1,2) In the course of further studies on the constituents of Gardenia species, we have now examined the iridoid constituents from the leaves of G. jasminoides cv. fortuneana HARA. This plant does not bear medicinal fruit, and there is no report, so far as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 18 publications
(17 reference statements)
1
22
0
Order By: Relevance
“…In the 1 13 C NMR spectrum of were very similar to those of 6-O-methyl deacetylasperulosidic acid methyl ester 16) , except that the absence of an ester methoxy signal at C-11, suggesting that possesses the structure, 6-O-methyl deacetylasperulosidic acid. However, compound exhibited the 1 16) . These differences in chemical shift for H-1 and H-9 signals, and in the coupling constant for H-1 doublet signal, indicated that the relative stereochemistry and the dihedral angle between H-1 and H-9 in could be different from those of 6-Omethyl deacetylasperulosidic acid methyl ester.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…In the 1 13 C NMR spectrum of were very similar to those of 6-O-methyl deacetylasperulosidic acid methyl ester 16) , except that the absence of an ester methoxy signal at C-11, suggesting that possesses the structure, 6-O-methyl deacetylasperulosidic acid. However, compound exhibited the 1 16) . These differences in chemical shift for H-1 and H-9 signals, and in the coupling constant for H-1 doublet signal, indicated that the relative stereochemistry and the dihedral angle between H-1 and H-9 in could be different from those of 6-Omethyl deacetylasperulosidic acid methyl ester.…”
Section: Resultsmentioning
confidence: 74%
“…The 1 H NMR spectrum displayed signals at d H 7.38 (1H, s), corresponding to an enol ether system conjugated with a carboxyl group, and at d H 5.84 (1H, br s), due to a sp 2 methine proton of a double bond in the five-membered ring, as found in various iridoid glycosides [7][8][9][15][16][17] . In the 1 13 C NMR spectrum of were very similar to those of 6-O-methyl deacetylasperulosidic acid methyl ester 16) , except that the absence of an ester methoxy signal at C-11, suggesting that possesses the structure, 6-O-methyl deacetylasperulosidic acid. However, compound exhibited the 1 16) .…”
Section: Resultsmentioning
confidence: 99%
“…The fruits of Gardenia jasminoides Ellis (Rubiaceae) (Chinese herbal name is Zhi Zi) has been used for the remedy for hepatic pain due to cirrhosis, abdominal pain due to dysentery, anti-phlogistics, diuretic, laxative, choleretic, and homeostatic purposes in the treatment of trauma by external application [1]. The major effective constituents of Gardenia fruits are iridoid glycosides such as geniposide, gardenoside, shanzhiside, scandoside methyl ester, deacetyl-asperulosidic acid methyl ester and genipin-1-␤-d-gentiobioside [2][3][4][5][6][7][8]. These compounds may be responsible for the biological activities of this drug [9][10][11][12][13][14] and their rapid and accurate purification is of great significance in the quality control of this natural drug and its formulations.…”
Section: Introductionmentioning
confidence: 99%
“…fortuneana HARA. 10) Loganin (S-5) and 7-ketologanin (S-6) were obtained from the leaves of Lonicera caerulea var.…”
Section: Methodsmentioning
confidence: 99%